Identifying Code Mixing in the Social Media Conversation (Instagram and Whatsapp) - Tsamratul Aeni (Journal of English Education, 2019)
This researcher aims to determine the types and dominant types of code mixing used by sixth semester students of English Language Education Study Program at Cokroaminoto Palopo University. This research used a qualitative method. The instrument of this research was documentation. The result of this research indicates that (1) there are 64 codes mixing which is used by sixth semester students. The students used 4 types of code mixing. Those are 30 codes mixing in the form of word (46.9%); 28 codes mixing in the form of phrase insertion (43.8%); 5 codes mixing in hybrid insertion form (7.8%); and there is only 1 code mixing in the form of a reduplication/repetition insertion (1.5%). (2) The dominant type of code mixing used by the students is in the form of word insertion.